(untitled) - Nguyen, Thi Mai Huong (Ha Noi, 2010)
SAVY 2 data provided a comprehensive picture of the youth Vietnam today as well as their changes compared with there same cohorts 5 years ago. SAVY 2 helps us see the aspects related to the development of youth such as education, employment, heath. Besides the positive signs, SAVY 2 also shows young people were facing the challenge to adapt to extensively transformed social and economic environment
Keywords: Youth,Thanh niên; Vietnam